Complete mitochondrial genome of Limnophyes minimus (Diptera: Chironomidae). Issue 1 (2nd January 2022) - Fang, Xiangliang; Li, Xintong; Lu, Tian; Fu, Jun; Shen, Mi; Xiao, Yunli; Fu, Yue
Abstract: The complete mitochondrial genome of Limnophyes minimus (Meigen 1818) was sequenced and annotated, and its general features and base composition were analyzed. The phylogenetic relationships of the families Chironomidae, Simuliidae, Sciaridae and Culicidae based on 25 metagenomes were reconstructed using maximum likelihood (ML) methods based on the concatenated nucleotide sequences, the phylogenetic analysis showed that L. minimus belongs family Chironomidae, which is consistent with the traditional morphological classification.